2011
DOI: 10.3945/ajcn.110.001917
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PGC-1α, a nodal regulator of mitochondrial biogenesis

Abstract: Mechanisms responsible for energy management in the cell and in the whole organism require a complex network of transcription factors and cofactors. Peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) has emerged as a master regulator of mitochondrial biogenesis and function, thus becoming a crucial metabolic node. We present an overview of the mechanisms by which PGC-1α is regulated, including the transcriptional regulation of PGC-1α expression and the fine-tuning of its final activity via po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
820
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,021 publications
(853 citation statements)
references
References 64 publications
28
820
0
5
Order By: Relevance
“…PGC-1α is the master regulator of mitochondrial biogenesis and energy expenditure (Fernandez-Marcos and Auwerx, 2011). The previous study using rat model reported that maternal high-fat intake led to a significant reduction in offspring hepatic PGC-1α mRNA expression (Burgueño et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1α is the master regulator of mitochondrial biogenesis and energy expenditure (Fernandez-Marcos and Auwerx, 2011). The previous study using rat model reported that maternal high-fat intake led to a significant reduction in offspring hepatic PGC-1α mRNA expression (Burgueño et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1a is a master transcription cofactor regulating mitochondrial biogenesis and function that is itself regulated by transcription and extensive posttranslational modifications 11,28 . Consistent with the dysfunction of the mitochondria, both mRNA and protein levels of PGC-1a are reduced in Wps/Wps BAT before the appearance of the obese phenotype (Fig.…”
Section: Scf/kit Expression Is Altered In Obese Animals and Humansmentioning
confidence: 99%
“…Peroxisome proliferatoractivated receptor-g (PPARg) coactivator-1a (PGC-1a, encoded by the Ppargc1a gene) has emerged as the master regulator of mitochondrial biogenesis and function 11 . PGC-1a activates mitochondrial biogenesis through stimulating mitochondrial transcription factor A (TFAM) and nuclear respiratory factors (NRFs), key regulators of mitochondrial DNA (mtDNA) replication/transcription 12 .…”
mentioning
confidence: 99%
“…At the same time, this research has uncovered new levels of complexity in transcriptional regulation mediated by PGC-1 coactivators. Of the three founding members of the family, PGC-1α has received the most attention, partly because of the many and highly regulated mechanisms that determine its activation and biological activity (comprehensively reviewed in [2,3]). More recently, work from several laboratories has shown that transcription of a single PGC-1α (also known as PPARGC1A) gene is controlled by several promoter regions that, coupled to alternative splicing, give rise to coactivator variants with distinct transcript and protein structure.…”
Section: Introductionmentioning
confidence: 99%